Enraizamento de ramos de mamoeiro (Carica papaya L.) obtidos for cultivo in vitro de ápices caulinares - SCHMILDT, EDILSON ROMAIS; TEIXEIRA, SILVIO LOPES; CRUZ, COSME DAMIAO; COUTO, FLÁVIO ALENCAR DE ARUAJO; LANI, ELIZONETE RIBEIRO GARCIA (Revista Ceres, 2015)
.